2013
DOI: 10.1075/ssol.3.1.06dji
|View full text |Cite
|
Sign up to set email alerts
|

Reading other minds

Abstract: The potential of literature to increase empathy was investigated in an experiment. Participants (N = 100, 69 women) completed a package of questionnaires that measured lifelong exposure to fiction and nonfiction, personality traits, and affective and cognitive empathy. They read either an essay or a short story that were equivalent in length and complexity, were tested again for cognitive and affective empathy, and were finally given a non-self-report measure of empathy. Participants who read a short story who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(95 citation statements)
references
References 22 publications
7
80
1
7
Order By: Relevance
“…Fictional narratives create an opportunity to simulate complex social interactions and exercise everyday social cognitive skills (Mar and Oatley, 2008), as well as to understand underlying mental processes in social situations (Oatley, 2013). In line with this, recent research suggests that both lifetime (Mar, Oatley, Hirsh, dela Paz, and Peterson, 2006;Mar, Oatley, and Peterson, 2009;Mar, Tackett, and Moore, 2010) and even a single exposure (Djikic, Oatley, and Moldoveanu, 2013;Kidd and Castano, 2013) to literary fictions can enhance TOM capacity. Moreover, TOM responses seem to be sensitive to how the narrative is presented.…”
Section: Theory Of Mindmentioning
confidence: 60%
“…Fictional narratives create an opportunity to simulate complex social interactions and exercise everyday social cognitive skills (Mar and Oatley, 2008), as well as to understand underlying mental processes in social situations (Oatley, 2013). In line with this, recent research suggests that both lifetime (Mar, Oatley, Hirsh, dela Paz, and Peterson, 2006;Mar, Oatley, and Peterson, 2009;Mar, Tackett, and Moore, 2010) and even a single exposure (Djikic, Oatley, and Moldoveanu, 2013;Kidd and Castano, 2013) to literary fictions can enhance TOM capacity. Moreover, TOM responses seem to be sensitive to how the narrative is presented.…”
Section: Theory Of Mindmentioning
confidence: 60%
“…Other recent findings suggest that reading fiction is related to empathic ability while reading non-fiction is not (Djikic et al 2013;Mar et al 2006;Mar et al 2009). Mar et al (2006), for instance, found that readers who were more familiar with fiction, as attested to by their correct recognition of the names of fiction authors (the Author Recognition Test, ART), also had higher scores on the »Reading the Mind in the Eyes Test« (Eyes Test) in which respondents have to infer emotional states from pictures of actors' eyes.…”
Section: Effects: the Evidencementioning
confidence: 99%
“…When it comes to the impact of reading stories on empathy, several studies demonstrated positive effects on various empathic measures, like role-taking ability, motivation for pro-social behavior and altruistic conduct (Adler/Foster 1997;Bilsky 1989;Djikic/Oatley/Moldoveanu 2013;Johnson 2012;2013;Mar et al 2006;Mar et al 2009;Shapiro/Morrison/Boker 2004). In Bilsky's (1989) experiment, for instance, high school students were randomly assigned to read one of two stories, or asked to do some quiet work on their own (control group).…”
Section: Effects: the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have observed that familiarity with fiction is positively correlated with mentalising performance, that is, people's ability to understand the mental states of others (Djikic, Oatley, & Moldoveanu, 2013;Mar, Oatley, Hirsh, dela Paz, & Peterson, 2006;Mar, Oatley, & Peterson, 2009). These correlational findings suggest that reading fiction and mentalising may involve overlapping cognitive abilities.…”
mentioning
confidence: 99%